DM-FS: A Comprehensive Database on Death-Modulated Fatal Shootings - Jacob Verrey (Scientific Data)
Abstract In the USA, officers and civilians engage in fatal encounters, situations in which a member of one group is slain at the hands of the other. Research on fatal encounters spans disciplines and can save lives, yet it tends to draw from databases that may be partial, unidirectional, and contain methodological differences. To remedy these issues, we propose a database on Death-Modulated Fatal Shootings (DM-FS). DM-FS makes five substantial contributions, and we highlight three. First, DM-FS is bidirectional. It is one of the few databases that enable the empirical exploration of how death in one group, police, affects deaths in another, fatally shot civilians and vice-versa. Second, DM-FS is comprehensive. It contains the entire universe of applicable agencies between January 1, 2015, and December 31, 2020. Third, it may be less partial than the status quo. Its rigorous validation procedures detected and corrected discrepancies between existing databases of fatally shot civilians: Fatal Encounters, Mapping Police Violence, Washington Post. DM-FS use cases are explored, such as in policymaking, modeling, and psychology.